Influence of nail biting and finger sucking habits on the oral carriage of Enterobacteriaceae - Firoz G Kamal; Reginald Ajay Bernard (Wolters Kluwer Medknow Publications, 2015)
Background: Oral habits like thumb sucking and nail biting are pernicious habits that act as an adaptive function in obtaining pleasure and subduing anxiety. These habits may also act as carriers of numerous microorganisms into the oral cavity, of which, Enterobacteriaceae members are transient pathogens, which might result in debilitating systemic conditions. Aim: To study the oral carriage of Enterobacteriaceae in children having habit of nail biting and thumb sucking. And to study the association of the organism with the individual's respective plaque indices. Subjects and Methods: Totally, 40 chronic nail biters, 40 chronic thumb suckers, and 20 controls (no habit) (8-15 years old) were enrolled in the study. Appropriate history and their plaque indices recorded. Sterile containers were used to collect the salivary samples and later cultured on Agar plates. Biochemical tests categorized the organisms into subspecies. Statistical Analysis Used: ANNOVA, Student's t-test. Results: Presence of a nail biting habit indicated a higher plaque index, which in turn showed a higher carriage of Enterobacteria spps, predominantly Escherichia coli. Conclusions: Oral surgical intervention in individuals with pernicious oral habits need to be counseled and educated on the possible complications, which might otherwise provide an environment that disseminates these microorganisms resulting in a broad range of local and systemic infections.